2017
DOI: 10.1002/brb3.841
|View full text |Cite
|
Sign up to set email alerts
|

Maternal separation affects expression of stress response genes and increases vulnerability to ethanol consumption

Abstract: IntroductionMaternal separation is an early life stress event associated with behavioral alterations and ethanol consumption. We aimed to expand the current understanding on the molecular mechanisms mediating the impact of postnatal stress on ethanol consumption.MethodsIn the first experiment (T1), some of the pups were separated from their mothers for 6 hr daily (Maternal Separation group ‐ MS), whereas the other pups remained in the cage with their respective mothers (Control group ‐ C). In the second experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 74 publications
4
22
0
Order By: Relevance
“…Furthermore, ethanol consumption is affected by dopaminergic neurons in the VTA projecting to the NAc, which alters GABAergic transmission. Several studies have reported that MS increases pup vulnerability to ethanol during adolescence, inducing an increase in ethanol consumption [ 83 , 84 ]. These findings mirror the phenomena in humans who suffer child abuse and neglect in early life, showing higher morbidity of drug abuse and alcoholism.…”
Section: Alterations In Behaviors Induced By Msmentioning
confidence: 99%
“…Furthermore, ethanol consumption is affected by dopaminergic neurons in the VTA projecting to the NAc, which alters GABAergic transmission. Several studies have reported that MS increases pup vulnerability to ethanol during adolescence, inducing an increase in ethanol consumption [ 83 , 84 ]. These findings mirror the phenomena in humans who suffer child abuse and neglect in early life, showing higher morbidity of drug abuse and alcoholism.…”
Section: Alterations In Behaviors Induced By Msmentioning
confidence: 99%
“…Among reports it is evident that, while performing LDB test, light chamber parameters have been considered over the dark box parameters [6]. As a result, distance travelled in the dark chamber, total distance travelled in the apparatus, and other behaviors were not taken into consideration (in fact it remained unknown at least in some experiments) when this test was conducted manually [17,21,39,44]. Many a times, researchers have to perform additional tests to get an idea about animal locomotion even after conducting LDB test.…”
Section: Discussionmentioning
confidence: 99%
“…Sarwar et al [42] has conducted the test by videotaping the rat behavior in the apparatus, but rat's activity in the dark compartment has not been reported. Although these reports demonstrated the use of technology for conducting LBD test, in some of the very recent reports it can be observed that this test has been performed entirely manually [17,21,39,44]. These methodological variations make it difficult to replicate or compare the results different laboratories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rodent study on postnatal maternal separation found that offspring demonstrated increased vulnerability to ethanol consumption during adolescence with enhanced expression of key genes associated with HPA axis functioning ( de Almeida Magalhães, Correia, de Carvalho, Damasceno and Brunialti Godard, 2017 ). A separate rodent study found that maternally separated offspring demonstrated a strong preference for ethanol, elevations in ACTH and corticosterone during a lab stressor, and that the ethanol consumption was correlated with the stress response ( Huot et al, 2001 ).…”
Section: Hpa-axis and Prenatal Substance Exposure In Clinical Studiesmentioning
confidence: 99%